FACTORS ANALYSIS AFFECTING BURNOUT AND SELFESTEEM IN THE GUIDANCE IMPLEMENTATION AS A TASK OF BUDDHIST EDUCATION TEACHERS - Hesti Sadtyadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to find out the factors and indicators that influence “burnout” and Self-Esteem in the guidance implementation as a task of Buddhist education teachers. This research is research and development, and the research subjects are Buddhist education teachers in Central Java Indonesia. The result of the study shows that the factors that influence “burnout” and Self-Esteem in the guidance implementation as a task of Buddhist education teachers are consisted of eight components, namely: additional tasks, classroom atmosphere, conflict, ambition, policy/rules, teaching success, self -esteem, and work-pressure. Indicators that influence each factor in guiding include: Additional tasks consist of four indicators, classroom atmosphere consists of four indicators, conflict consists of four indicators, ambition consists of four indicators, policy/rules consists of four indicators, teaching success consists of three indicators, Self-esteem consists of three indicators, and the work-pressure consists of three indicators.